Long term follow-up of patients with ventricular high rate events detected on remote monitoring of pacemakers - Ameesh Isath; Vaibhav Vaidya; Vidhushei Yogeswaran; Abhishek Deshmukh; Samuel Asirvatham; David Hayes; Suraj Kapa (Indian Pacing and Electrophysiology Journal, 2019)
Aims: Previous data suggest ventricular high rate episodes (VHREs) on pacemakers are frequent and not associated with overall mortality on short term follow up. We sought to determine whether VHREs are associated with mortality, device upgrade, or change in ejection fraction on long term follow up. Methods: A single center, retrospective study was performed on 542 patients with permanent pacemakers followed between 2011 and 2013. Follow-up was extended to 2017 for determination of long term outcomes. “True” VHREs were defined as episodes adjudicated to be due to non-sustained ventricular tachycardia on review of electrograms and “false” VHREs were defined as supraventricular arrhythmias or noise. Results: VHRE occurred in 202(37.2%)/542 included patients. True VHRE was detected in 148(27.3%) while 54(10%) had false VHRE. The mean age of the population was 72 ± 15 years and 46% were women. Mean follow-up was 3.3 ± 1.4 years. The baseline characteristics of the true, false and no VHRE patients were similar. There was no difference in all-cause mortality between groups (27% mortality in true VHRE, 33% in false VHRE and 29% in no VHRE). Furthermore, there was no difference between groups with regards to any device upgrade (5% any upgrades in the VHRE, 9% in false VHRE and 5% in no VHRE.) On follow up, EF declined in all groups: −4% vs −2.4% vs −3.5% for true, false and no VHRE. Conclusion: VHRE are frequently encountered on remote monitoring of pacemakers and not associated with increased risk of mortality or need for downstream device upgrade. Keywords: Non-sustained ventricular tachycardia, Pacemakers, Remote monitoring, Mortality